“Am I obligated to help?”: Emotions in the transnational enactment of Filipino family obligation and utang na loób in remittance-sending - Grava, Genevieve; Elizabeth, Vivienne; Keil, Moeata (New Zealand Sociology, 2026)
Much of what sociologists know about family obligation is derived from literature based on western populations and using a western lens, such as the study of Finch and Mason (1991, 1993). Although of some relevance to non-western families and individuals, this literature has limited utility when it comes to understanding the experiences of Filipinos and other migrants who emanate from collectivist cultures. To explore this gap in the literature, this article examines the remittance-sending practices of Filipino migrants in New Zealand to show how their ‘doing of family’ (Morgan, 2011) continues to be governed by traditional norms of family obligation from the home country. While the transnational context within which Filipino migrants do family affords the re-working of understandings of family and family obligation across spatial and temporal divisions (Yeoh, Huang & Lam, 2005), in this paper, we demonstrate that such re-workings are constrained by deeply ingrained Filipino cultural and family norms and the effects of governing emotions, like love, shame and guilt.